A brief motivational interviewing as an adjunct to periodontal therapy—A potential tool to reduce relapse in oral hygiene behaviours. A three‐year study. Issue 2 (24th August 2017) - Stenman, J; Wennström, JL; Abrahamsson, KH
Abstract: Objectives: To evaluate (ii) whether inclusion of a single motivational interviewing (MI) session, as an adjunct to periodontal therapy, might be beneficial for preventing relapse in oral hygiene behaviours among patients treated for chronic periodontitis and (ii) whether individual and clinical characteristics can be of predictive value for retention of sufficient oral hygiene behaviours. Material & methods: This 3‐year follow‐up of a previously reported randomized controlled trial (RCT) study of 6‐month duration included 26 patients. Patients in the test group had received one MI session by a clinical psychologist before initiation of the periodontal treatment. Otherwise, all patients followed the same treatment protocol for conventional educational intervention and non‐surgical periodontal therapy. Efficacy variables assessed for evaluation of the standard of self‐performed periodontal infection control were marginal bleeding index (MBI; primary efficacy variable) and plaque score (PI). Results: The patterns of change in MBI and PI scores were similar for test and control groups over the observation period. At 3 years, both groups showed a desirable mean full‐mouth MBI of 15%, a figure that was comparable to that at the short‐term evaluation after active periodontal treatment. The post‐treatment MBI was the only variable identified as a predictor of retained adequate oral hygiene behaviours. Conclusion: A single MI session as an adjunct to conventional periodontal therapy could not be proven to be of long‐term beneficial additive effect with regard to prevention of relapse in oral hygiene behaviour. Desirable standard of self‐performed infection control after active periodontal treatment predicted the retention of sufficient oral hygiene behaviour over time.